Speaking from Within Science: Vatican II’s Legacy in John Paul II’s Letter to George Coyne - Grygiel, Wojciech P. (Verbum Vitae, 2026)
This study examines how the Second Vatican Council’s teaching on science finds a mature and influential expression in John Paul II’s “Letter to Reverend George V. Coyne, S.J., Director of the Vatican Observatory” (hereafter cited as Letter to Coyne). The Council affirmed the autonomy of the sciences, encouraged dialogue with contemporary culture, and called for renewed theological engagement with a world shaped by scientific inquiry. The Letter to Coyne develops these principles with greater clarity and precision and is well-suited to the scientific community because it begins from within the scientific outlook and speaks in a manner that resonates with the concerns and methods of scientists. For this reason, it becomes a particularly effective medium for transmitting the message of Vatican II to those for whom scientific inquiry is a daily practice. The Letter presents a vision of complementary competences between theology and the natural sciences, proposes that theology benefit from methodological insights of scientific work, and articulates a model of mutual purification in which each discipline contributes to the integrity of the other. The study also situates the Letter within John Paul II’s intellectual formation and the circumstances of its composition. Finally, it suggests that the text has contributed to an intellectual climate more favorable to interdisciplinary research in fields such as cognitive science and artificial intelligence.